Challenges in smoking prevention among healthcare workers - Alharbi, Shada Murshed; AlTurki, Mona Moneer; Almutib, Alwaleed Khalid; Subahi, Esraa Jamel; Tayeb, Raghda Khaled; Alruwaili, Maha Nahi; Alatiyyah, Abrar Talal; Alali, Mohammed Talib; Alsuhaymi, Ibrahim Mohsen; Alzahrani, Mohammed Ali; Bantan, Saja Jamal (International Journal Of Community Medicine And Public Health, 2021)
Many diseases have been reported in association with smoking, including chronic obstructive pulmonary disease, lung cancer, and coronary artery disease. Healthcare workers (HCWs) play an essential role in such campaigns being in the first-line of management of the corresponding patients. Therefore, it is essential to investigate the smoking status among HCWs to make sure adequate interventions are appropriately delivered to their patients. Unfortunately, different studies in the literature indicate that the prevalence of smoking is high among HCWs. Furthermore, adopting restricting policies against smoking has been reported to be of limited efficacy in reducing the frequency of smoking. Therefore, other pharmacological therapies have been proposed. However, the duration of the effectiveness of these modalities does not allow for favorable long-term outcomes. Accordingly, psychological interventions, web-based campaigns, and person-to-person interviews can be the most appropriate modalities to achieve better outcomes. Further investigations are still needed for further validation of the most optimal and suitable intervention.